2008
DOI: 10.1111/j.1750-3841.2008.00752.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Headspace Aroma Compounds of Freshly Brewed Arabica Coffees and Studies on a Characteristic Aroma Compound of Ethiopian Coffee

Abstract: A sampling method to isolate headspace volatiles of freshly brewed drip coffee using a solid-phase microextraction fiber (fiber type: divinylbenzene/carboxen/polydimethylsiloxane) in a short time (2 min) immediately after extraction has been developed. Volatile compounds and potent odorants obtained from each headspace aroma of various arabica coffee extracts (3 production countries: Ethiopia, Tanzania, and Guatemala; 3 roasting degrees for each country: L26, L23, and L18) using the sampling method were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 35 publications
5
57
0
Order By: Relevance
“…Czerny et al (1999) found that attributes such as roasted, earthy, and smoky increased with degree of roasting. Akiyama et al (2008) reported smoke/roast, phenolic, sweet/caramel, and green to be positively correlated with degree of roasting, while sweet/fruity and acidic attributes to be negatively correlated. Sarrazin et al (2000) reported 'roasted biscuit', 'peanut', 'caramel', 'toasted bread', and 'cereal' to be the sensory notes for light roasted coffee.…”
Section: Discussionmentioning
confidence: 99%
“…Czerny et al (1999) found that attributes such as roasted, earthy, and smoky increased with degree of roasting. Akiyama et al (2008) reported smoke/roast, phenolic, sweet/caramel, and green to be positively correlated with degree of roasting, while sweet/fruity and acidic attributes to be negatively correlated. Sarrazin et al (2000) reported 'roasted biscuit', 'peanut', 'caramel', 'toasted bread', and 'cereal' to be the sensory notes for light roasted coffee.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the compounds being investigated, particularly the volatile terpenes, have not previously been quantified accurately although their presence and peak abundance have been reported previously (Del Terra et al, 2013, Gonzalez-Rios et al, 2007, Mondello et al, 2005, Akiyama et al, 2008. Mostly found in coffee flowers and berries, terpenes are known to remain in the roasted coffee beans and corresponding brews (Stashenko et al, 2013, Emura et al, 1997, Akiyama et al, 2008. As known contributors the boquet of wines and beers, these monoterpenes are also likely to influence coffee flavour.…”
Section: Application Of Analytical Methods To Measure Key Aroma Volatmentioning
confidence: 99%
“…The separation is based on partitioning or distribution of a sample between a moving (mobile) phase (gas), and a fixed or stationary phase (Wittkowski and Matissek, 1993). In combination with a GC, chemical detection of coffee flavour compounds can be conducted such as via a flame ionisation detector (FID) (Ribeiro et al, 2010, Ribeiro et al, 2012 or mass selective detector (MSD) (Akiyama et al, 2007, Akiyama et al, 2008. However, coupling a GC to a Mass Spectrometer (MS) has been reported to provide several advantages in flavour research due to its high sensitivity detection and the faster scan rates required for the GC peaks identification and traces analysis (McNair and Miller, 1998).…”
Section: Determination Of Key Volatile Aroma Compounds In Coffeementioning
confidence: 99%
See 2 more Smart Citations